Viscoelastic Damping in alternate reciprocating contacts - Carmine Putignano (Nature Portfolio, 2017)
Abstract Reciprocating motion between viscoelastic solids occurs in a number of systems and, in particular, in all the dampers which exploits, as a physical principle, the viscoelastic dissipation. So far, any attempt to predict the behavour of this field of dampers relies on approximate methodologies and, often, on a steady-state approach, with a consequent poor understanding of the phenomenon. Here, we develop a methodology capable of simulating the actual mechanics of the problem and, in particular, we shed light on how the presence of not fully relaxed viscoelastic regions, during the punch motion, determine the viscoelastic dissipation. The latter is shown to be dependent ultimately on two dimensionless parameters, i.e. the maximum speed in the cycle and the frequency. Finally, the importance of considering a rough interface is enlightened.